Agricultural growth linkages in Ethiopia: Estimates using fixed and flexible price models - Diao, Xinshen; Fekadu, Belay; Haggblade, Steven; Taffesse, Alemayehu Seyoum; Wamisho, Kassu; Yu, Bingxin (International Food Policy Research Institute, 2007)
Accelerating growth and poverty reduction, and the ultimate achievement of structural transformation, are the critical policy challenges in present day Ethiopia. This paper examines relevant growth options in terms of their impact on overall growth and poverty reduction in the country. It deploys a fixed-price semi-input-output model and a flexible-price economy-wide multi-market model for that purpose. The paper finds that agricultural growth can induce higher overall growth and faster poverty reduction than non-agricultural growth, although the latter can also have large growth effects in some cases. Among sub-sectors within agriculture, staple crops have stronger growth linkages. Decomposition of these effects also reveals that consumption linkages are much stronger than production linkages, i.e., the impact of increased consumption demand due to growth (agricultural and non-agricultural) is much larger than that of the corresponding expansion in input demand. Moreover, non-agricultural sectors have to grow in order to match growing supply of agricultural products and increasing demand for non-agricultural products. Otherwise, falling relative prices of agricultural products may dampen the realized gains in growth and poverty reduction.